Engaging end-users to maximise uptake and effectiveness of a new species recovery assessment: the IUCN Green Status of Species - Grace, MK; Timmins, HL; Bennett, EL; Long, B; Milner-Gulland, E; Dudley, N (Medknow Publications, 2021)
When developing a novel conservation assessment, tradeoffs between generality and precision, and between realism and simplicity, will inevitably need to be made. Engaging potential end-users during development can help developers navigate these tradeoffs to maximise uptake. End-user engagement can also produce feedback about external perceptions, allowing changes to be made prior to the final design. Here, we report on end-user consultations about the species recovery assessment method introduced by the International Union for Conservation of Nature (IUCN), which is a new component of the IUCN Red List of Threatened Species. This species recovery assessment was originally called the 'Green List of Species.' We conducted two types of end-user consultation over a two-year period—1) key informant interviews, and 2) technical consultations about the details of the assessment method, including identification of factors that increased the amount of time required to conduct an assessment. A main finding from the key informant interviews was that the name 'Green List of Species' was inappropriate for the assessment, given the potential for misunderstanding the scope of the assessment and potential confusion with the IUCN Green List of Protected and Conserved Areas. We therefore proposed the name 'Green Status of Species', a suggestion accepted by IUCN. A repeated concern in key informant interviews was the perception that the species recovery assessments were complex, indicating a potential tradeoff between scientific rigour and simplicity. To address this concern, we used feedback from the technical consultations to identify assessment steps which were most in need of refinement, and implemented solutions and made recommendations to streamline those steps (e.g., we found that the number of spatial units used in an assessment was positively correlated with assessment time, and increased greatly when more than 15 spatial units were used). This process of end-user engagement makes it much more likely that the Green Status of Species will be used in conservation communication, monitoring, and decision-making—helping achieve the ultimate goal of biodiversity recovery.